From Mothering Without a Net to Mothering on the Net: The Impact of an Online Social Networking Site on Experiences of Postpartum Depression - Mulcahy, Caitlin M.; Parry, Diana C.; Glover, Troy D. (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
This research speaks to the desire expressed by women, health care professionals, and researchers alike, for an alternative, non-pharmacological or therapy-related intervention for postpartum depression (PPD). Interviews with twenty-two mothers and members of Momstown.ca—a social networking site focused on connecting mothers online and face-to-face—demonstrated new mothers are increasingly isolated and without community. However, mothers reported becoming members of Momstown allowed them to build a social network providing them company, camaraderie, and community, resulting in improved mental health. We conclude services like Momstown could be viable, alternative interventions for women with ppd, enabling mothers to survive and thrive postpartum.